Unprecedented Unidirectional Chiral Luminescence and Self‐Assembly Morphologies‐Mediated Multifarious Circularly Polarized Phosphorescence From Au(I)‐Based Enantiomers - Debin Fu; Shanting Liu; Xiaofei Yang; Zhao Chen; Sheng Hua Liu (Aggregate)
ABSTRACT Realizing circularly polarized luminescence (CPL) with the same chiral direction by chiral luminogenic molecules under the identical conditions is unprecedented. Meanwhile, obtaining circularly polarized phosphorescence (CPP) with a large dissymmetry factor (glum) is highly significant but rather challenging. Herein, two chiral Au(I)‐containing enantiomers, namely (S,S)‐1 and (R,R)‐1, are prepared. (S,S)‐1 and (R,R)‐1 show different self‐assembly behaviors as the degree of aggregation in solution changes, leading to the formation of a variety of CPP signals. Notably, non‐mirror‐image CPP, CPP with the high glum values of +2.78 × 10−2 and −1.54 × 10−2, chirality amplification and inversion from the two chiral Au(I) luminogens are accompanied by the variation of their self‐assembly morphologies. Impressively, (S,S)‐1 and (R,R)‐1 exhibit aggregation‐induced CPP with the same chiral direction, and this is the first time that the unidirectional CPL from chiral enantiomers under the identical external environment is observed. Their respective three polymorphic crystals of (S,S)‐1 and (R,R)‐1, each with different packing arrangements, are fortunately obtained. The polymorphs derived from (S,S)‐1 or (R,R)‐1 demonstrate both M‐helix and P‐helix stacking arrangements. Through investigating their CPP properties, stacking modes, and intermolecular interactions of these six types of crystals cultivated by (S,S)‐1 and (R,R)‐1, the mechanism of their self‐assembly morphologies‐dependent multiple patterns CPP characteristics of (S,S)‐1 and (R,R)‐1 is further understood. Additionally, both (S,S)‐1 and (R,R)‐1 show a force‐triggered CPP quenching feature, and the chiral co‐assembly system with the |glum| value reaching 0.11 is gained by a combination of the synthesized enantiomers and commercial achiral liquid crystal.